Association of registered nurse and nursing support staffing with inpatient hospital mortality. Issue 1 (7th August 2019) - Needleman, Jack; Liu, Jianfang; Shang, Jinjing; Larson, Elaine L; Stone, Patricia W
Abstract : Background: The association of nursing staffing with patient outcomes has primarily been studied by comparing high to low staffed hospitals, raising concern other factors may account for observed differences. We examine the association of inpatient mortality with patients' cumulative exposure to shifts with low registered nurse (RN) staffing, low nursing support staffing and high patient turnover. Methods: Cumulative counts of exposure to shifts with low staffing and high patient turnover were used as time-varying covariates in survival analysis of data from a three-campus US academic medical centre for 2007–2012. Staffing below 75% of annual median unit staffing for each staff category and shift type was characterised as low. High patient turnover per day was defined as admissions, discharges and transfers 1 SD above unit annual daily averages. Results: Models included cumulative counts of patient exposure to shifts with low RN staffing, low nursing support staffing, both concurrently and high patient turnover. The HR for exposure to shifts with low RN staffing only was 1.027 (95% CI 1.002 to 1.053, p<0.001), low nursing support only, 1.030 (95% CI 1.017 to 1.042, p<0.001) and shifts with both low, 1.025 (95% CI 1.008 to 1.043, p=0.035). For a model examining cumulative exposure over the second to fifth days of an admission, the HR for exposure to shifts with low RN staffing only was 1.048 (95% CI 0.998 to 1.100, p=0.061), low nursing support only, 1.032 (95% CI 1.008 to 1.057, p<0.01) and for shifts with both low, 1.136 (95% CI 1.089 to 1.185, p<0.001). No relationship was observed for high patient turnover and mortality. Conclusion: Low RN and nursing support staffing were associated with increased mortality. The results should encourage hospital leadership to assure both adequate RN and nursing support staffing.